University student's dental and maxillofacial fractures characteristics and epidemiology in sports - Ivan Onone Gialain; Neide Pena Coto; Reinaldo Brito Dias (Universidade Estadual de Maringá, 2014)
Current study analyzes the characteristics and epidemiology of oral and nasal fractures and knowledge degree regarding the use of a mouthguard by an amateur university handball team inBrazil.  A cross-sectional study comprised 138 students who practiced the sport. They were interviewed on dental and nasal fractures and on the need of mouthguards in games such as amateur handball. Data were processed by descriptive analysis. Results showed that 19.6% had suffered some type of dental injury during the practice of sports, namely 40 fractured teeth; 12% had fractured nasal bones; 57% underwent head and neck injuries; 32% were unaware of the need to use a mouthguard during sports; 68% had heard of mouthguards, but only 4.5% of the interviewees made use of this protection device. There was a high prevalence of nasal and dental fractures in the group under analysis. The upper central incisors were most susceptible to fracture. Even though most athletes knew a mouthguard was needed during sports activities, only 4.5% actually used one.